2015
DOI: 10.1016/j.celrep.2015.04.038
|View full text |Cite
|
Sign up to set email alerts
|

Lineage-Specific Viral Hijacking of Non-canonical E3 Ubiquitin Ligase Cofactors in the Evolution of Vif Anti-APOBEC3 Activity

Abstract: SUMMARY HIV-1 encodes the accessory protein Vif, which hijacks a host Cullin-RING ubiquitin ligase (CRL) complex as well as the non-canonical cofactor CBFβ, to antagonize APOBEC3 antiviral proteins. Non-canonical cofactor recruitment to CRL complexes by viral factors, to date, has only been attributed to HIV-1 Vif. To further study this phenomenon, we employed a comparative approach combining proteomic, biochemical, structural, and virological techniques to investigate Vif complexes across the lentivirus genus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
70
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(76 citation statements)
references
References 71 publications
(108 reference statements)
6
70
0
Order By: Relevance
“…However, HIV-1 and SIV Vifs need the cofactor CBF-␤ to stabilize and form this complex (51,52), whereas FIV and other nonprimate lentiviruses (e.g., maedi-visna virus [MVV], caprine arthritis encephalitis virus, and bovine immunodeficiency virus [BIV]) Vifs do not require CBF-␤ to induce A3 degradation (53)(54)(55)(56). A recent study demonstrated that BIV Vif appears to operate independently of any cofactors, whereas MVV Vif hijacks cellular cyclophilin A as a cofactor in reconstituting the E3 ligase complex (53). Whether FIV Vif recruits any additional protein is unclear.…”
mentioning
confidence: 99%
“…However, HIV-1 and SIV Vifs need the cofactor CBF-␤ to stabilize and form this complex (51,52), whereas FIV and other nonprimate lentiviruses (e.g., maedi-visna virus [MVV], caprine arthritis encephalitis virus, and bovine immunodeficiency virus [BIV]) Vifs do not require CBF-␤ to induce A3 degradation (53)(54)(55)(56). A recent study demonstrated that BIV Vif appears to operate independently of any cofactors, whereas MVV Vif hijacks cellular cyclophilin A as a cofactor in reconstituting the E3 ligase complex (53). Whether FIV Vif recruits any additional protein is unclear.…”
mentioning
confidence: 99%
“…The Vif molecules of lentiviruses are important for viral replication, inactivating host antiviral factors of cytidine deaminases (APOBEC3) (32,(72)(73)(74). These lentiviral Vif proteins have evolved to use different strategies for overcoming their host's APOBEC3 (7,38,39,75). HIV-1 Vif assembles the CRL5 E3 ubiquitin ligase to induce the polyubiquitination and proteasome-mediated degradation of APOBEC3 (17,30,(76)(77)(78)(79)(80); this assembly is regulated by CBF␤ (14,(23)(24)(25)(26)(27)(28)39).…”
Section: Discussionmentioning
confidence: 99%
“…HIV-1 Vif assembles the CRL5 E3 ubiquitin ligase to induce the polyubiquitination and proteasome-mediated degradation of APOBEC3 (17,30,(76)(77)(78)(79)(80); this assembly is regulated by CBF␤ (14,(23)(24)(25)(26)(27)(28)39). In contrast, BIV Vif assembles with the CRL2 E3 ubiquitin ligase to induce the polyubiquitination and proteasome-mediated degradation of bovine APOBEC3, and BIV Vif activity is not regulated by CBF␤ (7,38,39). Surprisingly, we have discovered that BIV Vif is a potent inhibitor of HIV-1 replication, and this inhibition was manifested even in the absence of the antiviral factor APOBEC3.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations